Phenotypic Characterization of Jhum Rice (Oryza sativa L.) Landraces Collected from Rangamati District in Bangladesh (Bangladesh Rice Journal, 2018)
Genetic diversity of 30 Jhum rice landraces was studied under irrigated condition through Mahalanobis D2 statistic for agro-morphological characters. The landraces were grouped into five clusters. The intercluster distances were higher than intra-cluster distances indicating wider genetic diversity among the landraces of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The principal component analysis exposed that the first five components with vector values > 1 contributed 81.14% of the total variations. The highest number (8) of landraces was observed in cluster IV and the lowest (4) in cluster II. The intra-cluster distance was maximum in cluster III (1.62) containing six landraces and minimum in cluster I (0.57) having six landraces. The highest inter cluster value was 23.44 (between cluster II and V) and the lowest was 7.29 (between cluster III and IV). The highest flag leaf length, leaf area index, filled grains per panicle were found in cluster V while the lowest culm diameter, short duration, low yielding genotypes were clubbed into cluster II. Dwarf stature and lower flag leaf length were recorded into cluster I whereas the highest plant height and panicle length were obtained from cluster IV. Based on canonical vector analysis, culm diameter, days to flowering, days to maturity and length-breadth ratio had maximum contribution towards genetic divergence. Selection of parents from the clusters II and V followed by hybridization would possibly result in desirable transgressive segregants. Finally, Jhum rice landraces need to be conserved in Genebank for future breeding programmeBangladesh Rice j. 2017, 21(1): 47-57